2014
DOI: 10.1099/jmm.0.071167-0
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution and antifungal susceptibility profile of Candida isolates from bloodstream infections in Lima, Peru

Abstract: Yeast identification and in vitro susceptibility testing provide helpful information for appropriate administration of antifungal treatments; however, few reports from the Latin American region have been published. The aim of this study was to identify the species present in isolates from bloodstream infections diagnosed in nine hospitals in Lima, Peru and to determine their in vitro susceptibility to four antifungal drugs. We tested and identified 153 isolates collected between October 2009 and August 2011 us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
3
11
1
5
Order By: Relevance
“…Similar results were reported by other researchers (14,20,(24)(25)(26) (26). They also reported that all strains of C. parapsilosis were susceptible to caspofungin, while 1% and 1.2% of C. parapsilosis isolates from Latin America and North America, respectively, were resistant to anidulafungin (26).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were reported by other researchers (14,20,(24)(25)(26) (26). They also reported that all strains of C. parapsilosis were susceptible to caspofungin, while 1% and 1.2% of C. parapsilosis isolates from Latin America and North America, respectively, were resistant to anidulafungin (26).…”
Section: Discussionsupporting
confidence: 88%
“…No resistance to azole drugs was detected among the C. parapsilosis isolates. The current findings were in concordance with previous studies (13,14,19,20). On the other hand, the current results were different from Tortorano et al who documented a higher fluconazole resistance rate in C. tropicalis and C. parapsilosis isolates (25).…”
Section: Discussionsupporting
confidence: 81%
“…[36]. However, previous studies developed in Peru [37] and Brazil [38], with a small number of strains ( N = 8 and 15 isolates, resp.) did not find C. glabrata strains with AMB MIC > 1  μ g/mL.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with those of Khan et al, [31] who reported that the most effective drugs for their isolates were nystatin and amphotericin-B and with Taghizadeh et al, [32] who found that 95.6% of Candida species isolated from Bronchoalveolar Lavage samples was sensitive to nystatin. Also, Bustamante et al, [33] reported that 98.0% of the isolates were susceptible to amphotericin B.…”
Section: Discussionmentioning
confidence: 98%